AB0989 TUBERCULOSIS RISK IN CHILDREN WITH RHEUMATIC DISEASES TREATED WITH BIOLOGIC DISEASE MODIFYING ANTI-RHEUMATIC DRUGS. (2nd June 2020) - Kavadichanda, C.; M B, A.; Ajmani, S.; Maccora, I.; Balan, S.; Ramanan, A.; Agarwal, V.; Gupta, L.
Abstract : Background: Chronic rheumatic diseases entail the use of biologics in children. Immunosuppressive effects of drug therapy put children at risk of various infections. Tuberculosis (TB) is a leading chronic infection in certain parts of the world. Recent estimates suggest the prevalence of TB in India to be 3.2 cases per thousand population 1 . Objectives: Thus we reviewed the prevalence of Tuberculosis amongst children with various rheumatic disorders treated with different biologics. Methods: The search strategy for writing review articles proposed by Gasparyan et al 2 . was followed. Articles available on MEDLINE and Scopus, published on or after January 1, 2010 to 1 October 2019, were reviewed. (Figure 1 ) Details on Tuberculoisis and disease variables were collected (Table 1 ). Results: Data on infections in children with rheumatic disorders on biologics is scant (Table 2, Figure 2A ). Tuberculosis was reported on occasion (0-5 cases per country) in the developed world with the highest Tuberculosis reports being from Turkey (Figure 2B ). There is particular paucity of data from regions with highest number of incident cases or prevalence of tuberculosis more than 100 per 10 000 population (figure 2C, D). Retrospective studies of duration 10 m- 10years suggest that TB risk is minimal in pediatric rheumatology patients on biologics in low TB incident areas. However, most prospective studies suffer from short observation period (Table 2 ). Most registries focus on response to therapy rather than complications. Conclusion: TB risk is minimal with biologics use in peadiatric rheumatology in areas with low TB incidence (<99 cases per 10 000 population). However, most prospective studies are hampered by short observation period. There is insufficient data to establish safety in countries with high background prevalence of TB. Long term prospective national registries are needed from in TB countries with focus on risk factors for infections. References: [1]TB Statistics India | National, treatment outcome & state statistics [Internet]. TB Facts | TB, tests, drugs, statistics. [cited 2019 Jun 13]. Available from: https://www.tbfacts.org/tb-statistics-india/ [2]Gasparyan AY, Ayvazyan L, Blackmore H, Kitas GD (2011) Writing a narrative biomedical review: considerations for authors, peer reviewers, and editors. Rheumatol Int 31:1409– 1417. doi:10.1007/s00296-011-1999-3 Disclosure of Interests: Chengappa Kavadichanda: None declared, Adarsh M B: None declared, Sajal Ajmani Consultant of: Elly lily, Speakers bureau: J and J, Ilaria Maccora: None declared, Suma Balan: None declared, Athimalaipet Ramanan Consultant of: Abbvie, Eli Lilly, UCB, Novartis and SOBI, Speakers bureau: Abbvie, Eli Lilly, UCB, Novartis and SOBI, Vikas Agarwal: None declared, Latika Gupta: None declared